Tupelo Medical : managing price erosion - Anderson, Eric T., (SAGE knowledge. Cases., 2016)
Robert Davidson, pricing manager for Tupelo Medical, was concerned about the variability in price paid for its top-selling product, the Micron 8 Series blood pressure monitoring system. Using historical transaction data, this case explains how Davidson determines the appropriate price floor for the system.